2021
DOI: 10.3389/fcell.2021.640224
|View full text |Cite
|
Sign up to set email alerts
|

Eomes Impedes Durable Response to Tumor Immunotherapy by Inhibiting Stemness, Tissue Residency, and Promoting the Dysfunctional State of Intratumoral CD8+ T Cells

Abstract: Sustaining efficacious T cell-mediated antitumor immune responses in the tumor tissues is the key to the success of cancer immunotherapy. Current strategies leverage altering the signals T cells sense in the tumor microenvironment (TME). Checkpoint inhibitor-based approaches block inhibitory signals such as PD-1 whereas cytokine-based therapies increase the level of immune-stimulatory cytokines such as IL-2. Besides extrinsic signals, the genetic circuit within T cells also participates in determining the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…IL-33 has many biological functions that are involved both in the regulation of adaptive immune responses (Schmitz et al 2005 ; Schiering et al 2014 ; Bonilla et al 2012 ) and in tissue repair (Miller et al 2008 ; Jones et al 2010 ; Li et al 2014 ). Its role in tumors is under debate; in fact, on the one hand IL-33 can promote T cell antitumor activity (Villarreal et al 2014 ; Gao et al 2015 ), on the other, its expression has been associated with metastasis in several cancer models (Jovanovic et al 2014 ; Gillibert-Duplantier et al 2012 ; Liu et al 2014 ) and, accordingly, it is under study as a therapeutic target (Sun et al 2021 ). Fang et al observed that the overexpression or administration of IL-33 enhanced the growth of colon cancer cells, the formation of cell spheres, and the expression of stem cell genes (NANOG, NOTCH3 and OCT3/4) via phosphorylation of JNK (Fang et al 2017 ).…”
Section: Main Textmentioning
confidence: 99%
“…IL-33 has many biological functions that are involved both in the regulation of adaptive immune responses (Schmitz et al 2005 ; Schiering et al 2014 ; Bonilla et al 2012 ) and in tissue repair (Miller et al 2008 ; Jones et al 2010 ; Li et al 2014 ). Its role in tumors is under debate; in fact, on the one hand IL-33 can promote T cell antitumor activity (Villarreal et al 2014 ; Gao et al 2015 ), on the other, its expression has been associated with metastasis in several cancer models (Jovanovic et al 2014 ; Gillibert-Duplantier et al 2012 ; Liu et al 2014 ) and, accordingly, it is under study as a therapeutic target (Sun et al 2021 ). Fang et al observed that the overexpression or administration of IL-33 enhanced the growth of colon cancer cells, the formation of cell spheres, and the expression of stem cell genes (NANOG, NOTCH3 and OCT3/4) via phosphorylation of JNK (Fang et al 2017 ).…”
Section: Main Textmentioning
confidence: 99%
“…However, the expression of IFN-γ was significantly up-regulated in CD4 + and CD8 + T cells in Grm4 −/− mice (fig. S7G), suggesting that GRM4 regulates the same sets of genes in the tumor tissues and secondary lymphoid system ( 14 ). There were no statistical differences in the percentages of GZB-producing NK and CD8 + T cells (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the expression of immune checkpoint molecules characterizes T and NK cell exhaustion and may limit the efficacy of combination therapy ( Wherry, 2011 ; Wherry and Kurachi, 2015 ; Yang et al, 2020 ; Moesta et al, 2020 ; Bastid et al, 2015 ; Zhang et al, 2019 ; Sade-Feldman et al, 2019 ; Haas and Obenauf, 2019 ; Sun et al, 2021 ), we next looked at the expression of checkpoint molecules Tim-3, Lag-3, and CD39 by multi-color flow cytometry. The expression of all three inhibitory receptors was significantly enhanced on Foxp3 - CD4 + T cells, Tregs, CD8 + T cells, and NK cells after combination therapy ( Figures 4A–N ).…”
Section: Resultsmentioning
confidence: 99%
“…The strong stimulation provided by IL21 and PD-1 blockade on effector T cells may result in hyperactivation, a state that is characterized by the expression of multiple immune inhibitory receptors. These receptors prevent immune-mediated pathology, but limits the antitumor activity ( Alvarez-Fernández et al, 2016 ; Haas and Obenauf, 2019 ; Sade-Feldman et al, 2019 ; Sun et al, 2021 ). We showed that triple combination therapy with Tim-3 or Lag-3, and quadruple therapy, further increases the efficacy of double therapy.…”
Section: Discussionmentioning
confidence: 99%